2022
DOI: 10.1021/acsomega.2c02266
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductance of Charged Nanopores

Abstract: A nanopore’s response to an electrical potential drop is characterized by its electrical conductance, . For the last two decades, it has been thought that at low electrolyte concentrations, , the conductance is concentration-independent such that . It has been recently demonstrated that surface charge regulation changes the dependency to , whereby the slope typically takes the values α = 1/3 or 1/2. However, experiments have observed slopes of 2/3 and 1 suggesting that additional mechanisms, such as convec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…In recent years there has been an increased interest in the effects of surface charge regulation (SCR), whereby the surface charge (density) can be modulated by adsorption dynamics of ions onto the surface. [ 37,38,40,43–46 ] Briefly, in these works, it is shown that the surface charge density is a function of the bulk concentration, c 0 , pH, and other system parameters, such that σs(c0)c0α${\sigma }_s({c}_0)\sim c_0^\alpha $. Since the average excess concentration, Σ s , is linear with the surface charge density [Equation ()], the nanochannel resistance [ R nano c 0 / Σ s in Equation ()] is modified accordingly.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…In recent years there has been an increased interest in the effects of surface charge regulation (SCR), whereby the surface charge (density) can be modulated by adsorption dynamics of ions onto the surface. [ 37,38,40,43–46 ] Briefly, in these works, it is shown that the surface charge density is a function of the bulk concentration, c 0 , pH, and other system parameters, such that σs(c0)c0α${\sigma }_s({c}_0)\sim c_0^\alpha $. Since the average excess concentration, Σ s , is linear with the surface charge density [Equation ()], the nanochannel resistance [ R nano c 0 / Σ s in Equation ()] is modified accordingly.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%